Addressing the rising cause of death due to diseases of the circulatory system geared towards achieving SDG 3: evidence from data on medical certification of cause of deaths in Rajasthan State, India: 1999-2015 - Raut, Manoj Kumar; Sahu, Ananta Basudev (International Journal Of Community Medicine And Public Health, 2017)
Background: Medical certification of cause of death (MCCD) scheme is imperative tool to obtain scientific and reliable information in terms causes of mortality. The office of the registrar general of India (ORGI) initiated the scheme on MCCD under civil registration system (CRS), during the third five year plan. Methods: This paper analyzes the data for the last 16 years for MCCD in Rajasthan from 1999 to 2015. The findings are based on more than half a million deaths, for which cause of death data is reported. The per cent of cause of deaths have been computed and the curve estimation method has been used to project the cause of death due to circulatory diseases. Results: The data reveals that the percentage of medically certified deaths hovers around 10 to 13 percent during 1999 to 2015 of the total deaths registered under the civil registration system, which is about 5 million deaths. The highest percentage of deaths that has been medically certified is due to circulatory diseases as seen for the combined period of sixteen years (1999-2015) (21 percent) followed by deaths due to certain infectious and parasitic diseases (16 percent). This has increased from 13.8 per cent in 1999 to 20.2 per cent in 2015. This proportion has been projected upto 2030, the target year of achievement of Sustainable Development Goals (SDGs). Conclusions: Addressing this cause, could help in the achievement of indicator of 3.4.1, mortality rate attributed to cardiovascular disease, cancer, diabetes or chronic respiratory disease under the target of reducing by one third premature mortality from non-communicable diseases through prevention and treatment and promote mental health and well-being by 2030 subsumed under the SDG 3 of ensuring healthy lives and promote well-being for all at all ages.